Fibrinogen, Plasminogen Activator Inhibitor-1, and Carotid Intima-Media Wall Thickness in the NHLBI Family Heart Study - Folsom, Aaron R.; Pankow, James S.; Williams, Roger R.; Evans, Gregory W.; Province, Michael A.; Eckfeldt, John H. (Thrombosis and Haemostasis, 1998)
Several studies have linked higher plasma fibrinogen and plasminogen activator inhibitor (PAI-1) concentrations with increased risk of cardiovascular disease. We studied whether members of families with increased occurrence of coronary heart disease (CHD) have increased levels of fibrinogen and PAI-1 and whether subclinical carotid atherosclerosis is associated with these two hemostatic factors. Contrary to our hypothesis, fibrinogen and PAI-1 antigen levels were not different between high CHD risk families versus random families. Adjusted for age and family type, fibrinogen and PAI-1 were both associated positively with carotid intima-media thickness assessed by B-mode ultrasound. However, adjustment for lifestyle and medical covariates essentially eliminated these associations. These data suggest 1) elevated fibrinogen and PAI-1 do not explain clustering of CHD in families and 2) fibrinogen and PAI-1 may partly mediate the effects of other risk factors on carotid atherosclerosis, though the data are also consistent with them playing no causal role.